2014
DOI: 10.4172/2167-0951.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathogenesis of Alopecia Areata

Abstract: Alopecia areata (AA) is a recurrent, non-scarring type of hair loss affecting the hair follicles and sometimes the nails. Current evidence indicates that hair follicle inflammation in alopecia areata is caused by a T-cell mediated autoimmune mechanism occurring in genetically predisposed individuals. Environmental factors like infections, diet, vaccination and stress may be responsible for triggering the disease. The association between alopecia areata and other autoimmune diseases suggests that alopecia areat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…AA is a common nonscarring type of alopecia, which has different clinical presentations, classified according to the hair loss pattern or extent [37]. In some cases, AA is associated with other autoimmune diseases such as vitiligo, atopic dermatitis, diabetes, hypothyroidism, and pernicious anemia [39][40][41].…”
Section: Alopecia Areatamentioning
confidence: 99%
“…AA is a common nonscarring type of alopecia, which has different clinical presentations, classified according to the hair loss pattern or extent [37]. In some cases, AA is associated with other autoimmune diseases such as vitiligo, atopic dermatitis, diabetes, hypothyroidism, and pernicious anemia [39][40][41].…”
Section: Alopecia Areatamentioning
confidence: 99%
“…It is a common disease that affects 1%‐2% of population, with increased incidence between the second and fourth decades of life. It is frequently a common association with other autoimmune diseases such as vitiligo, atopic dermatitis, diabetes, hypothyroidism, and pernicious anemia . Chronic and recurrent cases of AA have been associated with emotional and psychological stress .…”
Section: Introductionmentioning
confidence: 99%
“…4 However, in a review study by Bhat et al, it is reported to account for 2-3% of the new dermatology cases in UK and USA, 3.8% in China, and 0.7% in India. 5 Both males and females are equally likely to be affected, but some studies reported male preponderance.…”
Section: Introductionmentioning
confidence: 99%